Pelatihan Manajemen dalam Peningkatan Produktivitas Pelaku UMKM di Desa Sanrobone, Kec Sanrobone, Kabupaten Takalar - Mappamiring P; Nurlaely Razak; Muh. Irfai Sohilauw; Hardiani Hardiani; Orfyanni S. Themba; Mursidah Mursidah; Yudi Ahmad Sadeli; Gunawan Gunawan; Husnul Agus Mubarak (Institut Teknologi dan Bisnis Semarang, 2024)
This training activity is a community service activity that aims to improve the ability of MSME actors in terms of business management to increase their business productivity. This training activity is a collaboration between STIEM Bongaya and Micro, Small and Medium Enterprises (MSMEs) partners in Sanrobone Village, Takalar. This activity was carried out on November 7, 2023 and was attended by 15 MSME business actors in Sanrobone Village. The implementation of these activities was carried out in stages, starting with the Socialization of Management Preparation Training to sharing sessions or discussions. Based on the results of the activities that have been described, the conclusions of the community service activities regarding management training in increasing the Productivity of MSME actors in Sanrobone Village, Sanrobone District, Takalat Regency are as follows: This activity aims to improve understanding of management management and increase the productivity of MSME actors. This training activity provides benefits in increasing productivity for MSME actors. Follow-up activities are expected to be more on continuous training techniques and mentoring for MSME actors.